IMPACT OF POLYMERS, DIFFERENT IRRIGATION PROGRAMS AND SELENIUM FOLIAR ON REDUCING AMOUNT OF IRRIGATION WATER FOR IRIS PLANTS - Istabraq. A. Aziz; Jawad, S. A. Abd Al-Latif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The experiment was carried out in one of the green houses of the research station A of the Department of Horticulture and Landscape Design during fall season 2020/2021 This study was aimed to reducing the amount of irrigation water using factorial experiment with in split plot designed by The study included three factor , First factor, the quality of irrigation water (main plots) and at three levels: (irrigation with water from the Tigris River 0.92 dm s-1(I0), alternating irrigation (one irrigation with saline water followed by irrigation with the water of the Tigris River(I1), Alternating irrigation (two irrigations with saline water, followed by irrigation with the water of the Tigris River(I2), Second factor was the addition of Polyacrylamide (0, 1.5,2.5) g of soil-1 his symbol(P0,P1.P2). Third factor was spraying with selenium with three concentrations (0, 10,20) mg L-1 his symbol (S0,S1,S2) The results showed The addition of polymers led to decrease in the amount of irrigation water used to irrigate Iris, as the amount of irrigation water decreased with an increase in the concentrations of added polymers. Also, the polymers contributed at a concentration of 2.5 g kg of soil-1 percentage of dry matter in leaves, percentage of carbohydrates in leaves, N, P, K, percentage the water potential in the leaves, relative water content, stomata area and the reduction in the activity of the enzyme Superoxide dismutase led to an increase in the salinity of the irrigation water to a decrease in all characteristics and an increases in the activity of the sod and spraying with selenium at a concentration of 20 mgL-1 increased all study parameters and reduced enzyme activityed.